ADRC‐based transient air/fuel ratio control with time‐varying transport delay consideration for gasoline engines. (June 2017) - Wang, Zhijing; Jiao, Xiaohong
Abstract : This paper presents a fuel injection controller based on the modified active disturbance rejection control (ADRC) algorithm to maintain the air/fuel ratio (AFR) at the stoichiometric value in the presence of a transport time delay. The factors affecting the dynamics of the AFR include the variations of the intake manifold pressure, engine speed, and load torque, as well as uncertain parameters existing in the fuel film evaporation and the oxygen sensor aging, which are viewed as the 'total disturbance' to the AFR system and estimated by the extended state observer (ESO). Thus, based on the Lyapunov–Krasovskii functional stability theory, the ADRC fuel injection controller is designed with the gain matrices of the controller and observer and solved by employing linear matrix inequalities. Considering the time‐varying transport delay, a time delay block is added to the ESO. By synchronizing the input signals of the ESO, the performance in terms of the timely compensation for the disturbance is improved. The effectiveness of the proposed control strategy is validated through simulation of a V6 spark ignition engine model developed by the Society of Instrument and Control Engineers (SICE) Research Committee on Advanced Powertrain Control Theory. © 2017 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.